A SOCIO-PRAGMATIC ANALYSIS ON UTTERANCES OF CRITICISM IN ARISTOCRATIC MOVIE MANUSCRIPT - HASTUTI, ANIS UMI (2011)
This research deals with criticizing utterances in Aristocratic movie manuscript. The aims of this research are to describe implication and describe politeness patterns of the criticizing utterances in aristocratic movie entitled King Arthur and Troy. The researcher employs the describe qualitative as a type of the research. The data source of this research is Aristocratic movie manuscript. The methods of collecting data are documentation the movie manuscript and observation of the films; gathering data criticism utterances and coding the data. The techniques of criticism analysis data of this research are analyzing implicature of criticism utterances use context of speech by Nunan, analyzing the politeness strategies of criticism utterances in King Arthur and Troy movies manuscripts by FTA (Face Threatening Art) and then discussing the findings. This study shows the variety of the implicature and politeness pattern of criticizing utterances used in Aristocratic movie manuscript. The implicature o9f criticism utterances are mocking, contradiction, order, disappointment, forbid, satire and anger. The politeness are baid on record, positive politeness, negative politeness and off-record.